1995
DOI: 10.1007/bf00665945
|View full text |Cite
|
Sign up to set email alerts
|

Hormone dependence of breast cancer cells and the effects of tamoxifen and estrogen:31P NMR studies

Abstract: Many breast tumors appear to progress from estrogen-dependent growth to a more malignant phenotype characterized by estrogen-independent growth, antiestrogen resistance, and a high metastatic potential. Utilizing 31P NMR spectroscopy on human breast cancer cells growing in vitro, we have investigated the effects of 17 beta-estradiol and tamoxifen on the metabolic/bioenergetic spectra of a series of human breast cancer cells that vary in their estrogen and antiestrogen responsiveness. A comparison of baseline s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…Indeed, the 3D and 2D constructs revealed differences in the fingerprints of the various cancer cell lines as well as different metabolic changes in response to chemotherapy. Treatment response studies have shown that cancer cells induced to form 3D spheroids are vastly less sensitive to chemotherapy than monolayer cells (30). In the current study, the LC 50 for CEM was higher by one order of magnitude than that of CGM.…”
Section: Discussioncontrasting
confidence: 45%
“…Indeed, the 3D and 2D constructs revealed differences in the fingerprints of the various cancer cell lines as well as different metabolic changes in response to chemotherapy. Treatment response studies have shown that cancer cells induced to form 3D spheroids are vastly less sensitive to chemotherapy than monolayer cells (30). In the current study, the LC 50 for CEM was higher by one order of magnitude than that of CGM.…”
Section: Discussioncontrasting
confidence: 45%
“…The similar cytotoxic profile of the crude extract against both HeLa (cervix cancer) and MCF-7 (breast cancer) cell lines followed by EACC might be attributed to their gynecological origin and hormone dependency [ 33 ]. Several gynecological solid tumors such as breast and cervix cancers are greatly influenced by hormone level and signaling within tumor micro milieu [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…While it is the second leading cause of cancer mortality among females, the pathogenesis of the disease remains unclear [Kuller, 1995;Ernster et al, 1996]. In the malignant progression of breast cancer, breast tumours progress from hormone-dependent growth to a more aggressive phenotype characterised by hormone-independent growth, resistance to endocrine therapy, and a frequently widespread metastases [Leonessa et al, 1992;Ruiz Cabello et al, 1995].…”
mentioning
confidence: 99%